A Powerful Place of Pictland: Interdisciplinary Perspectives on a Power Centre of the 4th to 6th Centuries ad. - NOBLE, GORDON; GONDEK, MEGGEN; CAMPBELL, EWAN; EVANS, NICHOLAS; HAMILTON, DEREK; TAYLOR, SIMON (Medieval Archaeology, 2019)
OUR UNDERSTANDING of the nature of late and post-Roman central places of northern Britain has been hindered by the lack of historical sources and the limited scale of archaeological investigation. New work at Rhynie, Aberdeenshire, Scotland (NJ 49749 26345), has begun to redress this through extensive excavation and landscape survey. This has revealed a Pictish central place of the 4th to 6th centuries ad that has European connections through material culture, iconography and site character. In addition to reviewing the place-name and historical context, this article outlines preliminary reflections on five seasons of excavation and survey in the Rhynie landscape. The article also provides a detailed consideration of chronology, including radiocarbon dating and Bayesian statistical analysis. The results reveal the multi-faceted nature of a major, non-hillfort elite complex of Pictland that comprised a high-status residence with cult dimensions, a major centre for production and exchange, and a contemporary cemetery. A series of sculptured stones stood in association with the settlement and cemetery and the iconography of the stones, along with the wider archaeological evidence, provides a rich dataset for a renewed consideration of the central places of early medieval northern Britain with broader implications for the nature of power and rulership in late and post-Roman Europe.